Response to 'What Do the Worldwide Governance Indicators Measure?' - Kaufmann, Daniel (2012)
Thomas (2009) dismisses the Worldwide Governance Indicators (WGI) as an 'elaborate and unsupported hypothesis' because of the failure to demonstrate the 'construct validity' of these indicators. We argue that 'construct validity' is not a useful tool to assess the merits of the WGI, and even if it were, Thomas provides no evidence of any practical consequences of failure to meet the criteria of construct validity.